PENGARUH PROMOSI, ONLINE CUSTOMER REVIEW, DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE (STUDI PADA MAHASISWA UNIVERSITAS BATAM) - Laga, Else Marieta; Luthfi, Andi M. (Zona Manajerial: Program Studi Manajemen (S1), 2021)
The purpose of this study is to find out and analyze the influence of Promotions, Online Customer Reviews, and E-Service Quality on Purchasing Decisions on Shopee e-commerce, a study at Students of Batam University. The method applied in this study is the quantitative method. The population in this study was students of Batam University with a total of 2,814 students at 2022. The sample of this study was 97 respondents. The data collection technique used in this study is a questionnaire which was tested for Validity and Reliability. The data analysis technique of this study uses Multiple Linear Regression, Classical Assumption Test, Hypothesis Test (t Test and F Test) and Coefficient of Determination. Data processing in this study used the SPSS Software version 25 program. The results of this study show that Promotion has a positive and significant effect on Purchasing Decisions on Shopee e-commerce for Batam University students with a probability value of 0,008 < 0,05. Online Customer Review has a positive and significant effect on Purchasing Decisions on Shopee e-commerce for Batam University students with a probability value of 0,015 < 0,05. E-Service Quality has a positive and significant effect on Purchasing Decisions on Shopee e-commerce for Batam University students with a probability value of 0,011 < 0,05. The value of the Coefficient of Determination of 49,0% shows the contribution of Promotion, Online Customer Review, and E-Service Quality to the Purchase Decision and the remaining 51,0% are explained by others relevant variables.